Implementation of Science and Technology for Regional Development: Improving the Quality of Ornamental Fish Production with a Concentration of Clove Oil Alternative to Sustainable Fishing Gear: Penerapan IPTEK Pengembangan Kewilayahan: Peningkatan Kualitas Produksi Ikan Hias dengan Konsentrasi Minyak Cengkeh Alternatif Alat Tangkap Lestari - Mauli Kasmi; Syamsul Marlin Amir; Andryanto Aman; Budiman Haruna; Arif Fuddin Usman (Yayasan Ahmar Cendekia Indonesia, 2022)
The Technology Improving the quality and quantity of ornamental fish depends on the catch production. System development of environmentally friendly fishing gear as an alternative to destructive fishing. The model developed by the PIPK team using clove oil concentration. Mastery of technological innovation, especially in handling techniques using injel ornamental fish fishing gear is still relatively low. The purpose of this program is to increase the results of the fishing community's business activities that are more economically independent, profitable and socially, as well as to improve soft skills and hard skills. Components in the clove oil and 95% alcohol concentration system with a composition of 1: 2. Supporting equipment to facilitate the determination of fishing locations using Garmin GPS to find efficient and effective fishing locations. The maintenance aquarium has a capacity of up to 1,500 liters of sea water with a rectangular shape. The method is to follow the direct process of handling ornamental fish with correct modular recirculation in both SMEs so as to produce quality ornamental fish products in a system of applying maintenance technology with a modular recirculation system efficiently and effectively. AbstrakTeknologi untuk Peningkatan kualitas dan kuantitas ikan hias injel tergantung dari hasil produksi tangkap. Sistem pengembangan alat tangkap ramah lingkungan sebagai alternatif destructive fishing. Model yang dikembangkan oleh tim PIPK dengan menggunakan konsentrasi minyak cengkeh. Penguasaan inovasi teknologi khususnya penanganan Teknik menggunakan alat tangkap ikan hias injel masih relative rendah. Tujuan Program ini adalah kegiatan ini dapat meningkatkan dipersivikasi produk masyarakat nelayan yang lebih mandiri secara ekonomi serta meningkatkan keterampilan soft skill dan hard skil. Komponen pada sistem konsentrasi minyak cengkeh dan Alkohol 95% dengan komposisi 1 : 2. Peralatan pendukung untuk memudahkan penentuan lokasi tangkap dengan menggunakan GPS Garmin untuk mencari lokasi tangkap yang efesien dan efektif. Aquarium pemeliharaan berkapasitas hingga 1.500 liter air laut dengan bentuk segi empat. Metodenya adalah mengikuti proses kegiatan langsung penanganan ikan hias injel dengan resirkulasi modular yang benar di kedua UKM sehingga mdnghasilkan kualiatas produk ikan hias injel pada sistem penerapan teknologi pemeliharaan dengan system resirkulasi modular secara efesien dan efektif.